(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The threat of the pandemic to the students and teachers results in having distance learning instead of the traditional classroom. These changes can be challenging, but on the other hand, they give students and teachers convenience. Distance learning, also known by various names such as distance education, e-learning, mobile learning, or online learning, is a form where teachers are physically separated from students during instruction and learning. Studying tourism with the help of e-learning may teach the skills and knowledge to be used in a country’s economic growth and development. The study focused on the educational system of tourism students. Referring to distance learning and using e-learning materials may help them improve their academic performance. This research explores the potential positive aims of e-learning on students’ academic performance. This study utilized a quantitative research method by using a descriptive research design. The researcher gathered data such as a survey questionnaire and stratified sampling technique to collect information from (80) random tourism students from Bestlink College of the Philippines to get the effects of e-learning materials on the academic performance of tourism students. The questionnaire developed contained four categories. The respondents chose one option for each question (Strongly Agree=4 points, Agree=3 points, Disagree=2 points, and Strongly Disagree=1 point). The raw data were carefully reviewed, tallied, and analyzed using Frequency, Percentage, and Weighted Mean. Most respondents are aged 21-25, belonging to a bracket of students in the young adult category. Furthermost of them are female, and graduating students are responded. The study shows no significant relationship between e-learning materials and tourism students’ academic performance at Bestlink College of the Philippines. All students taking up the Bachelor of Science in Tourism should know the significance of E-Learning in studying. The school administration should implement comprehensive feasibility on its functionality that will enhance the students’ learning by experience through E-Learning to develop their capabilities and knowledge. For the teachers/instructors/professors, explore more in sharing their expertise with the students to be able for them to put the theories into practice in the field of tourism even if they are using E-Learning. The owner should analyze the progress, performance, and effectiveness of the E-Learning Materials in the Academic performance of the Tourism Students to become competitive in the global market. The administration should continue the use of e-learning materials in selected subjects. Intuition gives freedom to the students to choose between online study and traditional study.